Post-Publication Responsibilities of a Journal Author - Surajit Bhattacharya; Neeta Bhattacharya; Kaushik Bhattacharya; Neela Bhattacharya (National Board of Examinations Journal of Medical Sciences)
Popularizing a scientific research paper after publication, so that it can get maximum exposure and citation, is a solemn responsibility of the researchers. They should aim to do so both among the scientific community as well as in the general public if there is a definite message for the masses. The scientific community can be informed by posts in academic networking sites (such as LinkedIn. ResearchGate and Mendeley), updating the departmental or institutional home page, and by ensuring that major abstracting and indexing services (e.g. Web of Science and Scopus) update the publication. The published articles reach a wider audience if they are in openaccess journals. To convert the research to the general public we must translate complex research into easily digestible formats for a wider audience beyond academia. We can then use multiple means like a press release highlighting key findings of the research, sharing the publication link, with a summary on social media platforms using relevant hashtags, create engaging visuals like infographics or video summaries. Every time the research is presented from the podium, the publication should be mentioned with a hyperlink, so that people can photograph it and visit it later. The more popular the research is, the more likely it will get cited.